Rarity Assessment of Lamproptera species (Papilionidae: Leptocircini) and the Modelling of their Distribution across Borneo - Nur Azizuhamizah, Idris (Universiti Malaysia Sarawak (UNIMAS), 2019)
Conservation planning and ecological research aimed at understanding patterns of biological diversity have focused on determining threatened and rare species. Much knowledge about the natural world has come from the study and observation of common species, yet a significant portion of species in the world are rare. Rare species may be at greater risk of extinction because of their small geographic ranges, low abundance and greater susceptibility to environmental changes. Species distribution modelling had been increasingly used to understand rare and endangered species distribution as well as environmental pressures affecting them. The aims of this study were to evaluate the rarity of the Lamproptera butterflies in Borneo, predict their potential distribution patterns and determine their conservation and potential threats to their survival. Subsequent to this, species occurrence data obtained from voucher specimens of Lamproptera butterflies deposited in UNIMAS Insects Reference Collection (UIRC), Research Development and Innovation Division (RDID) of the Sarawak Forest Department, and Centre of Insects Systematics (CIS), Universiti Kebangsaan Malaysia, an extensive literature reviews and field sampling were evaluated based on three rarity axis of Rabinowitz (1981) and vulnerability index proposed by Kattan (1992). The occurrence data were later analyzed in Maxent software in order to obtained the potential distribution of the Lamproptera species. In this study, both Lamproptera species are naturally rare species with suffusive pattern of rarity. The Lamproptera species scored ‘4’ in Kattan’s Vulnerability Index which mean they are rare in two criteria which are geographical distribution and population abundance. Majority of the high suitability area for the dragontail butterflies lie in the northwest part of Borneo. Environmental variables that affects the species distributions are temperature of annual range (Bio7), precipitation of driest month (Bio14), temperature seasonality (Bio4) and precipitation of wettest quarter (Bio16). Rarity assessment and distribution modelling are invariably connected. Thus, increasing knowledge on the status and distribution range regarding specific taxa provided much needed boost to our understanding of the population dynamics of these rare species.